Closed ventilation/anesthesia apparatus - John Dingley (1995)
Inventor:DINGLEY JOHN [GB]Applicant:UNIV WALES MEDICINE [GB]CPC:A61M16/00A61M16/0045A61M16/0075(+4)IPC:A61M16/00A61M16/10A61M16/22(+3)Publication info:US5979443 (A)1999-11-09Priority date:1995-06-08